Structural and electrical properties of magnetron sputtered Ti(ON) thin films: The case of TiN doped in situ with oxygen - Trenczek-Zajac, A.; Radecka, M.; Zakrzewska, K.; Brudnik, A.; Kusior, E.; Bourgeois, S.; de Lucas, M.C. Marco; Imhoff, L. (Journal of power sources, 2009)
Incorporation of oxygen into TiN lattice results in formation of titanium oxynitrides, TiO x N y that have become particularly interesting for photocatalytic applications. Elaboration as well as characterization of TiN and in situ oxygen-doped thin films is the subject of this paper. Thin films, 250–320 nm in thickness, have been deposited by dc-pulsed magnetron reactive sputtering from Ti target under controllable gas flows of Ar, N 2 and O 2. Optical monitoring of Ti plasma emission line at λ = 500 nm has been implemented in order to stabilize the sputtering rate. Scanning electron microscopy (SEM), X-ray diffraction in grazing incidence (GIXRD), micro-Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), optical spectrophotometry and four-point probe electrical resistivity measurements have been performed in order to follow evolution of film physical parameters as a function of the oxygen flow rate η O 2 at which the films were deposited. The relationship between η O 2 expressed in standard cubic centimetres per minute, sccm and the nitrogen/oxygen content in thin films has been established by means of the analysis of the XPS spectra. GIXRD studies indicate that incorporation of oxygen results in a progressive loss of preferential orientation in 〈1 1 1〉 direction, a change in the grain size from 16 nm for TiN to about 3 nm for films deposited at η O 2 = 1.32